Digital transformation in sports – currentе trendsы and trends - Lubysheva L.I. (Theory and Practice of Physical Culture, 2025)
The aim of the study is to identify trends and trends in the digital transformation of the sports industry based on content analysis of current publications of the journal "Theory and Practice of Physical Culture". Methodology and organization of research. In the course of the work, a content analysis of the publications of the journal "TandPFC" for the period 2024 was carried out. The item is selected as the invoice unit. A total of 28 articles were selected on the use of digital technologies in sports and physical education of students. Research results and conclusions. Based on the results of content analysis, the main trends in the development of digital transformation of physical culture and sports are identified: digitalization and virtualization in education, digitalization and virtualization in sports, gamification, artificial intelligence and machine learning. The current state of manifestation of the considered trends causes the formation of digital transformation trends, among which the key ones are: the use of wearable digital devices for monitoring the physical state of a person in education and sports, the use of mobile applications in training and managing the training process, the use of machine vision technologies in analyzing and modeling athlete movements, the development of.